Ensaios de adensamento de fluxo restringido e Ko em argila mole - Barbosa, Paulo Sérgio de Almeida (1990)
It is the main purpose of this study to evaluate the performance of restricted flow consolidation test carried out in Sarapuí soft clay. Standard incremental consolidation tests have also been performed and the results of these are been performed and the results of these are compared with results of restricted flow consolidation tests. Good agreement between results of these two types of tests has been obtained by a number of methods are compared. A triaxial Ko cell developed at COPPE/UFRJ and allowing anisotropic and isotropic consolidation besides shearing is presented. A Ko consolidation test in Kaolin is compared with an incremental test and good agreement is obtained between results of both tests.